Reductions in body measurements promoted by a garment containing ceramic nanoparticles: a 4‐month follow‐up study. (26th February 2013) - Conrado, Luis Augusto Lupato; Munin, Egberto
Summary Background Published literature reports significant improvements in pathological conditions, such as pain, blood dyscrasias, and cellulite, after using topical occlusive accessories containing particulate ceramic materials. Recent work reported a reduction in body measurements after 30 days of daily use of high‐waist undershorts made of synthetic fabrics with embedded ceramic particles. Objectives In this study, we investigated whether the use of a garment made with synthetic fibers embedded with powdered ceramic could lead to reductions in body measurements at a longer time span (120 day). Methods Thirty‐two female volunteers wore clothing containing ceramic powder for at least 8 h a day for 120 days. The efficacy of the treatment was evaluated through anthropometric measurements taken before treatment and after 30, 60, and 120 days of treatment. Results The experimental data showed a more pronounced reduction in body measurements at the beginning of treatment with a trend of stabilization in measured body circumferences during the final 60 days of the experimental period. Conclusions The experimental data showed that the occlusive treatment with a garment composed of ceramic particles promoted reductions in body measurements during a 120‐day experimental period.